Synaptic Dynamics of the Feed-forward Inhibitory Circuitry Gating Mechanical Allodynia in Mice. (May 2020) - Wang, Qun; Zhang, Xiao; He, Xiaolan; Du, Shibin; Jiang, Zhenhua; Liu, Peng; Qi, Lu; Liang, Chen; Gu, Nan; Lu, Yan
Abstract : Background: The authors' previous studies have found that spinal protein kinase C γ expressing neurons are involved in the feed-forward inhibitory circuit gating mechanical allodynia in the superficial dorsal horn. The authors hypothesize that nerve injury enhances the excitability of spinal protein kinase C γ expressing interneurons due to disinhibition of the feed-forward inhibitory circuit, and enables Aβ primary inputs to activate spinal protein kinase C γ expressing interneurons. Methods: Prkcg-P2A-tdTomato mice were constructed using the clustered regularly interspaced short palindromic repeats and clustered regularly interspaced short palindromic repeats-associated nuclease 9 technology, and were used to analyze the electrophysiologic properties of spinal protein kinase C γ expressing neurons in both normal conditions and pathologic conditions induced by chronic constriction injury of the sciatic nerve. Patch-clamp whole cell recordings were used to identify the nature of the dynamic synaptic drive to protein kinase C γ expressing neurons. Results: Aβ fiber stimulation evoked a biphasic synaptic response in 42% (31 of 73) of protein kinase C γ expressing neurons. The inhibitory components of the biphasic synaptic response were blocked by both strychnine and bicuculline in 57% (16 of 28) of neurons. Toll-like receptor 5 immunoreactive fibers made close contact with protein kinase C γ expressing neurons. After nerve injury, the percentage of neurons double-labeled for c-fos and Prkcg-P2A-tdTomato in animals walking on a rotarod was significantly higher than that in the nerve injury animals (4.1% vs. 9.9%, 22 of 539 vs. 54 of 548, P < 0.001). Aβ fiber stimulation evoked burst action potentials in 25.8% (8 of 31) of protein kinase C γ expressing neurons in control animals, while the proportion increased to 51.1% (23 of 45) in nerve injury animals ( P = 0.027). Conclusions: The Prkcg-P2A-tdTomato mice the authors constructed provide a useful tool for further analysis on how the spinal allodynia gate works. The current study indicated that nerve injury enhanced the excitability of spinal protein kinase C γ expressing interneurons due to disinhibition of the feed-forward inhibitory circuit, and enabled Aβ primary inputs to activate spinal protein kinase C γ expressing interneurons. Abstract : Using the clustered regularly interspaced short palindromic repeats/clustered regularly interspaced short palindromic repeats-associated nuclease 9 technique, a novel mouse strain was created allowing study of a key set of spinal interneurons. The data suggest hyperexcitability of spinal protein kinase C γ expressing interneurons facilitates allodynia after nerve injury.Supplemental Digital Content is available in the text.